Experimental verification of the program of improvement of physical training of officers-instructors at higher educational establishment of the Ministry of Internal Affairs of Ukraine - S. M. Bezpaliy (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Grounded, developed and tested efficiency of the program of officers-teachers' improvement in physical training. Borne change in organization of physical training, correlation of volumes of general and special physical training is changed, entered readings with a prophylactic and training orientation. The level of physical preparedness of teaching staff of higher institutes is investigational. In research took part 62 officers-teacher under the age of 40 years. The level of physical preparedness was determined on results at run on 100 meters, undercuttings on a cross-beam and runs on 1000 meters. It is set that employments on the experimental program were instrumental in more expressed growth of level of physical preparedness of teachers. A difference between the indexes of officers of experimental and control groups in speed qualities makes 0,12 seconds, in power qualities - 1,8 times, in endurance - 40,5 seconds.